2022
DOI: 10.1101/2022.01.18.476867
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metagenomics revealing molecular profiling of microbial community structure and metabolic capacity in Bamucuo, Tibet

Abstract: We performed a survey of the microorganisms in Bamucuo, Tibet, resulting in 160,212 (soil) and 135,994 (water) contigs by shotgun metagenomic methods. We discovered 74 new bacterial species and reconstructed their draft genomes, which were obtained from the 75 reconstructed almost complete metagenomic assembly genomes (MAG) in the soil and water samples. Proteobacteria and Actinobacteria were found to be the most dominant bacterial phyla, while Euryarchaeota was the most dominant archaeal phylum. To our surpri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 98 publications
(145 reference statements)
0
2
0
Order By: Relevance
“…Investigating the change in bacterial communities along the altitudinal gradient will shed light on the prediction of future climatic changes scenario (Yuan et al, 2014 ). Wei et al ( 2022 ) characterized the microbial community composition and metabolic capacity in Qinghai-Tibet Plateau high-altitude areas (with an altitude of 4,555 m) and confirmed that Qinghai-Tibet Plateau is a huge and valuable resource bank in which more new non-resistant antibiotics and many other bioactive substances could be developed. Characterizing the microbial community composition is important for forage preservation because phyllosphere microbial flora play a critical role in ensiling fermentation and provide sufficient fodder for local livestock during winter and spring.…”
Section: Introductionmentioning
confidence: 96%
“…Investigating the change in bacterial communities along the altitudinal gradient will shed light on the prediction of future climatic changes scenario (Yuan et al, 2014 ). Wei et al ( 2022 ) characterized the microbial community composition and metabolic capacity in Qinghai-Tibet Plateau high-altitude areas (with an altitude of 4,555 m) and confirmed that Qinghai-Tibet Plateau is a huge and valuable resource bank in which more new non-resistant antibiotics and many other bioactive substances could be developed. Characterizing the microbial community composition is important for forage preservation because phyllosphere microbial flora play a critical role in ensiling fermentation and provide sufficient fodder for local livestock during winter and spring.…”
Section: Introductionmentioning
confidence: 96%
“…Recently, one study reported only 20 MAGs from soil samples (>4500 a.s.l.) in the Tibetan Alpine Grassland (Wei et al, 2022). In our study, 96 non-redundant MAGs were obtained from all samples.…”
Section: Discussionmentioning
confidence: 99%